Endophytic Fungal Assemblages in Calophyllum and Garcinia spp. of Clusiaceae Family in Western Ghats, India - Ruma, Karmakar; Sekhar, Shailasree; K.K. Sampath, Kumara; Ramachandrappa Niranjana, Siddapura; Sripathy Prakash, Harischandra (Current Biotechnology, 2012)
A total of 596 fungal endophytes were isolated from 2000 bark and twig samples of five medicinal plants from Clusiaceae family of Western Ghats, India, during three seasons viz., rainy, winter and summer. The isolated endophytes belonged to different fungal classes which were Ascomycetes (0.6%), Coelomycetes (19.3%), Hyphomycetes (52.1%), Zygomycetes (1.3%) and Sterile mycelia (0.7%). The most frequently recovered endophytes were Pestalotiopsis sp., Trichoderma sp., Myrothecium sp., Acremonium sp., Fusarium oxysporum and Aspergillus niger. A few other species recovered were Aspergillus spp., Ascochyta sp., Botrytis cinera, Botryodiplodea theobromae, Chaetomium sp., Cladosporium sp., Colletotrichum spp., Fusarium spp., Morteirella sp., Nigrospora oryzae, Penicillium sp., Paecilomyces sp., Phyllosticta sp. and Verticillium sp. Endophytes recovery was significantly more during the rainy season than winter and summer seasons.
Keywords: G.morella